Suppose that a random variable X has a Poisson distribution with parameter λ. The
parameter λ itself is a random variable with the exponential distribution with mean 1
c ,
where c is a constant. Show that
P(X = k) =
c
(c + 1)k+1
"P\\left( X=k \\right) =\\int_0^{+\\infty}{P\\left( X=k|\\lambda =t \\right) f_{\\lambda}\\left( t \\right) dt}=\\int_0^{+\\infty}{\\frac{t^ke^{-t}}{k!}ce^{-ct}dt}=\\\\=\\frac{c}{k!}\\int_0^{+\\infty}{t^ke^{-\\left( c+1 \\right) t}dt}=\\left[ \\left( c+1 \\right) t=x \\right] =\\frac{c}{k!\\left( c+1 \\right) ^{k+1}}\\int_0^{+\\infty}{x^ke^{-x}dx}=\\\\=\\frac{c}{k!\\left( c+1 \\right) ^{k+1}}\\varGamma \\left( k+1 \\right) =\\frac{c}{\\left( c+1 \\right) ^{k+1}}"
Comments
Leave a comment